INFLUENTIAL FACTORS IN SELECTING A BACHELOR’S DEGREE FROM PRIVATE HIGHER EDUCATIONAL INSTITUTES IN SRI LANKA: A STUDY BASED ON UNDERGRADUATES OF INTERNATIONAL DEGREE PROGRAMMES - Abeygunawardena, K A (PEOPLE: International Journal of Social Sciences, 2018)
National University intake in Sri Lanka has become progressively competitive over the years and a small percentage of the student population is eligible for state-funded higher education. Therefore, a majority of the students who fail to enter National Universities and students who complete advanced level in British curriculum have been increasingly seeking alternative educational options in the domestic market due to the high cost in overseas education. As a result, international degree programmes (IDPs) have emerged through private higher educational institutes (PHEIs) to cater to the demand for university-level education in Sri Lanka. The main objective of this study is to uncover the influential factors in selecting a bachelor’s degree (BD) from IDPs which have emerged recently. Due to the flexibility and optionality in IDPs offered in Sri Lanka, the decision-making process in selecting a BD has become complex and multifactorial, which is evident through research studies carried out by critics including Sia (2011), Kusumawati, Yanamandram & Perera (2010) and Briggs (2006). Data for this study were collected from 420 first-year students of IDPs at randomly selected 7 PHEIs, where a questionnaire was administered with 59 predefined variables. Of those, 39 variables were identified as most influential variables by factor analysis and those were further grouped into 7 main factors namely, university characteristics, the source of information, programme evaluation, cost, marketing strategy, infrastructure facilities and peer influence. According to the research findings, the infrastructure facilities of the PHEIs have been rated as the most influential factor with 9 different variables. The contribution of the marketing strategy, university characteristics, costs, programme evaluation and source of information are also discovered and rated to be more influential than ‘peer’ influence. However, it was observed that the variables categorised under peer influence are with the highest factor loadings. The results of this study can be beneficial in optimising the enrolment strategies of PHEIs in Sri Lanka and in guiding prospective students on their choices in higher education.